Large spin hall angle enhanced by nitrogen incorporation in Pt films - Xu, Zhan (2022)
We report on the enhancement of spin Hall angle from the CoFeB/Pt interface by introducing nitrogen into the Pt thin film. Spin-torque ferromagnetic resonance measurements on the effective spin Hall angle (θSH) reveal a non-monotonic variation as a function of the amount of nitrogen gas introduced, Q in the film deposition, which peaks at θSH = 0.16 when Q is 8%. Our analysis shows that the θSH enhancement is mainly attributed to the increase in spin-dependent scattering at the interface. The effective magnetic damping decreases with increasing Q due to the reduced spin-orbit coupling. The interfacial spin transparency is also observed to show improvement after the introduction of nitrogen. Moreover, the additional damping-like torque from the interface may also lead to the enhancement of the linewidth modulation.